Migratory experiences of university students. Qualitative study at the National University of Córdoba (Praxis Educativa, 2019)
The main objective of the article is to share the analytical constructions on the migratory processes of university students of the National University of Córdoba (Argentina), who move from the interior of the province or from different points of the country to do their higher education in the city of Cordoba. It is intended to describe and interpret the experiences lived by students, from migration and during the first two years of arrival in this city, to reconstruct the meanings given to these experiences and analyze the integration process to the new space social. It is a qualitative study in which life stories of students of the Facultad de Filosofía y Humanidades are recovered. Some descriptions and interpretations are shared, elaborated around analytical dimensions such as space, time and relationships, aspects that are modified substantively since migration.
Keywords: Internal migration; students; higher education; qualitative analysis